Cerebrospinal fluid p-tau217 performs better than p-tau181 as a biomarker of Alzheimer’s disease - Janelidze, Shorena; Stomrud, Erik; Smith, Ruben; Palmqvist, Sebastian; Mattsson, Niklas; Airey, David C.; Proctor, Nicholas K.; Chai, Xiyun; Shcherbinin, Sergey; Sims, John R.; Triana-Baltzer, Gallen; Theunis, Clara; et al. (Nature communications, 2020)
Cerebrospinal fluid (CSF) p-tau181 (tau phosphorylated at threonine 181) is an established biomarker of Alzheimer’s disease (AD), reflecting abnormal tau metabolism in the brain. Here we investigate the performance of CSF p-tau217 as a biomarker of AD in comparison to p-tau181. In the Swedish BioFINDER cohort ( n = 194), p-tau217 shows stronger correlations with the tau positron emission tomography (PET) tracer [ 18 F]flortaucipir, and more accurately identifies individuals with abnormally increased [ 18 F]flortaucipir retention. Furthermore, longitudinal increases in p-tau217 are higher compared to p-tau181 and better correlate with [ 18 F]flortaucipir uptake. P-tau217 correlates better than p-tau181 with CSF and PET measures of neocortical amyloid-β burden and more accurately distinguishes AD dementia from non-AD neurodegenerative disorders. Higher correlations between p-tau217 and [ 18 F]flortaucipir are corroborated in an independent EXPEDITION3 trial cohort ( n = 32). The main results are validated using a different p-tau217 immunoassay. These findings suggest that p-tau217 might be more useful than p-tau181 in the diagnostic work up of AD. Cerebrospinal fluid (CSF) p-tau181 (tau phosphorylated at threonine 181) is an established biomarker of Alzheimer’s disease (AD) reflecting abnormal tau metabolism in the AD brain. Here the authors demonstrate that CSF p-tau217 shows better performance as an AD biomarker than p-tau181.